STATISTICAL CHARACTERISTICS OF TRACE ELEMENTS OF HIGH PURITY QUARTZ OF THE URALIAN TYPE (UFALEY QUARTZ VEIN AREA, SOUTH URALS) - A.N. Savichev; P.A. Krasilnikov (Минералогия)
High-purity quartz (HPQ) of the Uralian type is a hydrothermal-metasomatic variety of natural quartz, which has distinct genesis in comparison with other HPQ types. According to the results of statistical studies of economic quartz concentrates produced from HPQ of the Uralian type (vein no. 175 of the Kyshtym deposit of granular quartz), it is suggested that quartz concentrate inherits structural trace elements and mineral inclusions. Quantitative estimation of these trace elements is provided. The correlations between trace elements are caused by genetic features of hydrothermalmetasomatic quartz.